RELIGIOUS VIEWS ABOUT CRAFTSMANSHIP SAINTS IN FERGANA VALLEY (Scientific journal of the Fergana State University, 2023)
This article provides an overview of the religious views of Fergana valley craftsmanship Saints. The main focus in on demonstrating the reasons for the beliefs of Fergana valley regarding craftsmanship Saints. The views of a number of religious views on craft Saints are reflected.